In vitro screening of fungicides and plant extracts against six pathogenic fungi isolated from cotton (Gossypium arboreum L.) seed - Nahar, Mst Nazin; Shamsi, Shamim (Bangladesh Journal of Botany, 2020)
Six pathogenic fungi, namely Aspergillus flavus Link., A. niger van Tieghem (Type-I)., Curvularia lunata (Wakker) Boedijn, Fusarium moniliforme var. subglutinans Wr. & Reink., Fusarium sporotrichioides Sherb., Mem. and Rhizoctonia solani J.G. Kuhn were isolated from cotton seeds. Five fungicides viz., Acrobat MZ, Autostin 50 WDG, Capvit 50 WP, Nativo 75 WP and Thiovit 80 WG were selected to evaluate in vitro efficacy at 100, 200, 300, 400 and 500 ppm concentrations against pathogenic fungi following poisoned food technique. Out of 5 fungicides Nativo 75 WP showed the complete growth inhibition of above mentioned six pathogenic fungi at all the used concentrations. Autostin 50 WDG showed complete growth inhibition of all tested pathogenic fungi except Curvularia lunata. Leaf extract of five angiospermic plants viz., Adhatoda vasica, Aegle mermelos, Azadirachta indica, Datura metel and Psidium guajava were selected to evaluate in vitro fungitoxicity at 5, 10, 15 and 20% concentrations against the test pathogens. At 20% concentration, out of the 5 plants extracts A. indica was found to be most active to inhibit the growth of Aspergillus niger (Type-I) (65.56%) and Fusarium moniliforme var. subglutinans (75.00%), Psidium guajava were most active against A. flavus (81.29%) and Curvularia lunata (72.23%), and Datura metel was most active against Fusarium sporotrichioides (64.77%) and Rhizoctonia solani (42.44%).